2010
DOI: 10.1007/s10286-010-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Arterial baroreflex dysfunction in major depressive disorder

Abstract: Both the sensitivity and the number of times the arterial baroreflex is being active are reduced in major depressive disorder and this baroreflex dysfunction may prevail long-term when depressive symptoms have improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…[18][19][20][21][22][23] One of the plausible mechanisms explaining the relationship between depression and arrhythmia is autonomic dysfunction. Patients with depression have altered secretion of norepinephrine, a higher resting heart rate, low heart rate variability, and reduced baroreflex sensitivity, [23][24][25][26][27][28][29] resulting in resting sinus tachycardia. 25,26 There are numerous facts indicating a possible link between depression, arrhythmia, and outcome.…”
Section: Résumémentioning
confidence: 99%
“…[18][19][20][21][22][23] One of the plausible mechanisms explaining the relationship between depression and arrhythmia is autonomic dysfunction. Patients with depression have altered secretion of norepinephrine, a higher resting heart rate, low heart rate variability, and reduced baroreflex sensitivity, [23][24][25][26][27][28][29] resulting in resting sinus tachycardia. 25,26 There are numerous facts indicating a possible link between depression, arrhythmia, and outcome.…”
Section: Résumémentioning
confidence: 99%
“…Five of these studies reported a significant decrease in depression at the one-month follow up time point, in comparison to baseline severity (Hansen et al, 2011;Kayser et al, 2011;Minelli et al, 2014;Weeks et al, 2013;Yoosefi et al, 2014). Two observational studies ( Johansson et al, 2010;Kalogerakou et al, 2015) both reported a significant decrease in depression compared to baseline, at 8-9 weeks follow up and 6 months since the beginning of treatment respectively. Three studies compared levels of depression at follow up with depression at the end of the treatment period (Dukart et al, 2014;Meeter et al, 2011;Nordanskog et al, 2014).…”
Section: Changes In Depression Beyond the Treatment Periodmentioning
confidence: 99%
“…Forty seven of the 89 were observational studies (Azuma et al, 2011;Bär et al, 2010;Bayless et al, 2010;Beall et al, 2012;Bersani et al, 2014;Bilgen et al, 2014;Burgese & Bassitt, 2015;Casarotto et al, 2013;Chiaie et al, 2013;Dannlowski et al, 2013;Dukart et al, 2014;Ebert et al, 2010;Galletly, Paterson, & Burton, 2012;Goto et al, 2012;Guloksuz et al, 2015;Hu et al, 2010;Johansson, Ehnvall, Friberg, & Myredal, 2010;Joshi et al, 2015;Kalogerakou et al, 2015;Kautto et al, 2015;Lin et al, 2013;Loo, Mahon, Katalinic, Lyndon, & Hadzi-Pavlovic, 2011;Lucca et al, 2010;Lyden et al, 2014;McCall et al, 2013;Medda et al, 2014;Meeter, Murre, Janssen, Birkenhager, & van den Broek, 2011;Minelli et al, 2014;Nickl-Jockschat et al, 2015;Nordanskog, Larsson, Larsson, & Johanson, 2014;Ota et al, 2015;Oudega et al, 2011;Perrin et al, 2012;Piccinni et al, 2013;Rapinesi et al, 2015;Rapinesi et al, 2013;Royster et al, 2012;Saijo et al, 2010;Samuelsson, Gerdin, Öllinger, & Vrethem, 2012;Tendolkar et al, ...…”
Section: Focus and Design Of The 91 Studiesmentioning
confidence: 99%
“…Esses componentes arteriais são um dos principais sistemas para corrigir os desvios da PAM, agem tanto no ramo simpático (diminuindo sua atividade), quanto no ramo parassimpático (aumentando sua atividade) do sistema nervoso autônomo. Vários estudos demonstraram que a sepse afeta negativamente a sensibilidade desses receptores; e a perda da resposta destes reguladores é um dos principais determinantes de hipóxia e disfunção orgânica (50,164) . Segundo Godin e cols (165) De acordo com a literatura a sepse causa diversas alterações neurológicas, como por exemplo, o comprometimento do sistema nervoso autônomo (SNA) (50) .…”
Section: (Tabela 3)unclassified
“…Conhecidamente, uma disfunção do SNA pode desencadear um infarto do miocárdio, um estudo mostra que a análise dos componentes do SNA podem ser fatores prognósticos de uma parada cardíaca, independentemente da arritmia o FEVE (166) . Johansson e cols e Rucatti e cols (50,164,168) O tratamento com CTM-GW, poderia estar agindo no cérebro ou no sistema nervoso do animal séptico, quem por sua vez estaria atuando na regulação dos impulsos nervosos para manter a homeostase hemodinâmica. Entretanto, também poderia estar agindo na proteção ou suporte do SNA e na modulação dos astrócitos, sendo essas propriedades já descritas (169) .…”
Section: (Tabela 3)unclassified